Status of specific measles immunity among townspeople in Kharkiv region - Kalinichenko, Svitlana; Torianyk, Inna; Milentieva, Kristina; Antusheva , Tetyana; Moiseenko, Tetyana; Ovetchyn, Pavlo (Annals of Mechnikov’s Institute, 2022)
Introduction. The aggravation of the problem of epidemic monitoring of measles is caused by a number of problems, among which the formal attitude of the population to the prevention of this infection occupies the leading place. The lack of objective information on measles distorts not only its statistics, but also prevails over the use of adequate measures in extreme cases and the clinical management of patients in accordance with the nosological prototype.To predict the incidence of measles and the dynamics of the epidemic process, information about the actual protection of the vaccinated population against this infection is necessary. However, comprehensive multidimensional studies on the actual protection of the population, taking into account the manifestations of the epidemic process of infections controlled by immunoprophylaxis means, are not conducted in Ukraine. Meanwhile, for the quality and efficiency of the epidemiological surveillance system, namely its most essential component, the immunological monitoring, they are indispensable The aim: to study the status of specific measles immunity among residents in Kharkiv region. Materials and Methods. Determination of IgG class antibodies was carried out using enzyme-linked immunosorbent assay test systems for the quantitative determination of class G immunoglobulins to measles virus "Measles-IgG-MBA" (MedBioAlliance, Ukraine). To determine class G antibodies to the measles virus, a double binding method is used, based on the contact of the measles virus antigen, adsorbed on the surface of the wells of the tablet, with antibodies (IgG) of the tested serum samples.The research material was blood samples of persons, n= 387 (schoolchildren, post-graduate students) of both sexes, aged from 16 to 25 years. Procedural moments of blood sampling were carried out under the conditions of the manipulation rooms of the Kharkiv City Student Hospital of the Municipal Non-Profit Enterprise of the Kharkiv City Council. The participation of each person in the initiated study was agreed and ensured in accordance with the principles of medical ethics. Respondents were warned about possible risks and consequences. Biological material in special containers with appropriate documentation and in accordance with the rules was delivered to the laboratory of viral infections of the SA"IMI NAMN". Statistical data processing was carried out in accordance with the rules of ordinal and alternative variational statistics. To analyze the obtained results, they were grouped by attributive and variational features Results& Discussion. It was found that 87,2% of high school students and 57,4% of final year students had protective antibody titers. The results were consistent with the vaccination history and age of those studied. Further analysis of the anamnestic data revealed that the majority of undergraduates vaccinated according to an individual schedule between 12 months and 18 years of age had indeterminate antibody titers. Moreover, among those studied who had been vaccinated between the ages of 16 and 18 years, i.e., less than 7 years prior to the examination, there was not a single person who did not have protective antibody titers. The data obtained suggest that adults should be revaccinated every 10 years. Conclusion. Summarizing the results, we note that in the current conditions of the spread of bovine infection, the need for population-based anti-Core immunity studies is extremely relevant and will help to address the issues of supplementary immunization implementation.